Lessons from Operation Enduring Freedom - Tripp, Robert S., 1944-; Project Air Force (U.S.) (Santa Monica, CA : RAND, Project Air Force, 2004)
Presents an analysis of Air Force combat support experiences associated with Operation Enduring Freedom and compares these experiences with those associated with Operation Allied Force (OAF) to determine similarities and applicability of lessons across experiences.
An overview of JTF NA and OEF -- Combat support execution planning and control -- Forward operating locations and site preparation -- Forward support location/CONUS support location preparation for meeting uncertain FOL requirements -- Reliable transportation to meet FOL needs -- Resourcing to meet contingency, rotational, and MRC requirements.
"MR-1819."
Includes bibliographical references.
Also available in electronic form via the RAND Corporation Web site.
Keywords: United States. -- Air Force -- Supplies and stores; Airlift, Military -- United States; Operation Enduring Freedom, 2001-2014.; Operation Allied Force, 1999.; Kosovo War, 1998-1999.; Deployment (Strategy); Logistics; History